Combining Autologous Breast Reconstruction and Vascularized Lymph Node Transfer - Chang, Edward I.; Masià, Jaume; Smith, Mark L. (Seminars in Plastic Surgery, 2018)
Breast cancer patients are at risk for developing postmastectomy lymphedema syndrome of the ipsilateral upper extremity following treatment for breast cancer in the setting of an axillary dissection, postoperative radiation, and chemotherapy. For patients suffering from lymphedema who are also seeking breast reconstruction, combining an autologous abdominal free flap with a vascularized inguinal lymph node transfer provides patients the opportunity to have an aesthetic breast reconstruction as well as the potential to improve their lymphedema in a single operation. The present article aims to provide a description of the salient features of this approach including the preoperative preparation, the surgical technique, the postoperative management and complications, and a summary of the outcomes.
Keywords: vascularized lymph node transfer; breast reconstruction and lymph node transfer; breast free flap and lymphedema surgery; DIEP flap and lymph node transfer